Resilience and frailty among gynecological patients in oncological treatment: the chain mediating role of stigma and health literacy - Man, Shuo; Wu, Xiaofang; Huang, HaoWen; Yu, Jinjin; Xia, Ling (Frontiers in Psychiatry, 2025)
BackgroundFrailty poses a significant threat to the health status among gynecological patients in oncological treatment. Previous studies have shown that resilience, stigma, and health literacy are associated with frailty. However, their effects and potential relationship with frailty among gynecological patients in oncological treatment have not been fully studied.ObjectiveThe study aimed to explore the mediation role of stigma and health literacy between resilience and frailty among gynecological patients in oncological treatment.MethodsA total of 202 gynecological patients in oncological treatment in three gynecological wards of a tertiary hospital in Wuxi from March 2024 to May 2024 were selected for the study using a cross-sectional research method. A convenience sampling method was used. Information was collected on demographic characteristics, resilience, stigma, health literacy, and frailty. The PROCESS macro program was used to explore the mediating role of stigma and health literacy in the relationship between resilience and frailty.ResultsThe prevalence of frailty among gynecological patients in oncological treatment was 27.2%. The mediation effect results demonstrated that resilience was not a direct predictor of frailty (β = -0.010, 95%CI: -0.084 0.065) but indirectly predicted frailty through health literacy (β = -0.100, 95%CI: -0.155 -0.053) and stigma-health literacy (β = -0.056, 95%CI: -0.091 -0.029). However, no significant mediating effect of stigma alone was found (β = -0.038, 95%CI: -0.085 0.005).ConclusionsThe findings reveal the impact and potential relationship of resilience and frailty among gynecological patients in oncological treatment in patients with gynecologic oncology. Health literacy mediated the effect between resilience and frailty. Stigma and health literacy were chain mediators in the link between resilience and frailty. Healthcare professionals should pay timely attention to the psychological and mental status of gynecological patients in oncological treatment patients with gynecologic oncology and take measures to improve health literacy.